Adsorption and affinity of Escherichia coli to different aggregate sizes of a silty clay soil - Behrends Kraemer, Filipe B. (2013)
Fil: Behrends Kraemer, Filipe B. Universidad de Buenos Aires, Facultad de Agronomía, Departamento de Uso y Manejo del Suelo; Argentina.